ANARC: Active Light Source for Nighttime Absolute Radiometric Calibration - Qiu, Yanqian; Zhao, Bing; Zhou, Yifan; Yi, Yang; Wang, Kainan; Yin, Zhenping; Zhao, Lei; Muller, Detlef; Wang, Xuan; Hu, Xiuqing (IEEE geoscience and remote sensing letters, 2024)
The optical components of space-borne sensors are subject to environmental degradation, resulting in changing response characteristics, especially at different wavelengths. Consequently, the implementation of radiometric calibration is imperative to ensure the accuracy and reliability of the sensors. Calibration requires the capability to provide known excitations across the sensor's spectral range, which is difficult to achieve with the existing means. Thus, this letter proposes a ground-based multiwavelengths active light source for nighttime absolute radiometric calibration (ANARC), capable of generating light with a uniform intensity distribution, three monochromatic wavelengths, and variable intensity within the satellite detection field of view. The absolute intensity of ANARC is precalibrated by an unmanned aerial vehicle (UAV) equipped with an optical power meter. The atmospheric transmittance during satellite overpasses is measured by co-located lidar systems. We conducted two test experiments targeting the NOAA-20 satellite. The deviations of the top-of-atmosphere (TOA) ANARC emissivity from the measured emissivity from the Visible/Infrared Imaging Radiometer Suite Day Night Band were −8.06% and 1.02%, respectively. At the same time, ANARC can cover the dynamic range of the high gain stage in the low light band (LLB) of the moderate resolution spectral imager-low light (MERSI-LL) in FengYun-3 E. This preliminary verification suggests the feasibility of using ANARC for nighttime sensor calibration, which provides a new opportunity to improve radiometric calibration accuracy. It could also facilitate hyperspectral sensor calibration due to three monochromatic wavelengths of ANARC.